Poetry and style in Kalmyk heroic warrior tales - Mandzhieva, Bayrta B. (The New Research of Tuva, 2015)
Review to: Sarangov V.T. Poetry and style in Kalmyk heroic warrior fairy tales. Elista: Kalmyk University Press, 2015. 104 P.